Metabolite Profiling of Barley Grains Subjected to Water Stress: To Explain the Genotypic Difference in Drought-Induced Impacts on Malting Quality - Wu, Xiaojian; Cai, Kangfeng; Zhang, Guoping; Zeng, Fanrong (Frontiers in Plant Science, 2017)
Grain weight and protein content will be reduced and increased respectively when barley is subjected to water stress after anthesis, consequently deteriorating the malt quality. However such adverse impact of water stress differs greatly among barley genotypes. In this study, two Tibetan wild barley accessions and two cultivated varieties differing in water stress tolerance, were used to investigate the genotypic difference in metabolic profiles during grain-filling stage under drought condition. Totally 71 differently-accumulated metabolites were identified, including organic acids, amino acids / amines, and sugars / sugar alcohols. Their relative contents were significantly affected by water stress for all genotypes and differed distinctly between the wild and cultivated barleys. The PCA analysis of metabolites indicated that the Tibetan wild barley XZ147 possessed a unique response to water stress. When subjected to water stress, the wild barley XZ147 showed the most increase of β-amylase activity among the four genotypes, as a result of its higher lysine content, less IAA biosynthesis, more stable H2O2 homeostasis and more up-regulation of BMY1 gene. On the other hand, XZ147 had the most reduction of β-glucan content under water stress than the other genotypes, which could be explained by the faster grain filling process and the less expression of β-glucan synthase gene GSL7. All these results indicated a great potential for XZ147 in barley breeding for improving water stress tolerance.